THE EFFECT OF SHARIA FINANCIAL LITERATURE ON THE PERFORMANCE OF SHARIA BANKING EMPLOYEES PT. BANK SUMUT KC SHARIA MEDAN - Dimas Dwi Permana; Indah Lestari; Mutiah Khaira Sihotang (Proceeding International Seminar of Islamic Studies, 2022)
This Study aims to determine the effect of Demographic factor and Islamic Financial Literacy on the Performance of Islamic Banking Employee at PT. Sumut Syariah Bank Branch Office Medan. Data collection techniques in this study using a questionnaire, which is in the from of data collection techniques that are done by giving a set of questions and written statements to the respondent to be answered. Data analysis techniques used in this study were Validity Test, Reliability Test, Normality Test, Multicollinearity Test, Heteroscedasticity Test, t Test, f Test, Multiple Linear Regression and Determination Coefficient using SPSS 22.0. Based on the of the t test, Demographic Factor (X1) and Islamic Financial Literacy (X2) affect employee performance at PT. Sumut Syariah Bank Branch Office Medan. The results of the f test indicate that a significant value is smaller than 0.05, it can be concluded that Ha is accepted and Ho is rejected by the meaning that there is a joint effect on Demographic Factor (X1) and Islamic Financial literacy (X2) on Employee Performance, and the coefficient of Determination (R) is 80,6%, the effecy caused by Demographic Factor (X1) and Islamic Financial Literacy (X2) and 19,4% is influenced by other variables.